Esophageal squamous cell carcinoma in a backyard rooster - Leão, Philipe A.; Oliveira, Letícia B.; Santos, Willian H. M.; Moreira, Matheus V. L.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2019)
Squamous cell carcinoma, a malignant epithelial neoplasm originating from the epidermis squamous cells or the digestive mucosa epithelium, was diagnosed in an adult rooster. The rooster was lethargic and presented difficulties in swallowing. Physical examination revealed a large deep mass in the cranial cervical region. Due to poor prognosis, the bird was euthanized and then post mortem examined. Grossly, in the oral portion of the esophagus, there was a mass invading and partially occluding the lumen. Microscopically, the mass had neoplastic cells interconnected by evident desmosomes junctions and keratin pearl formations. Microscopic findings confirmed the diagnosis of squamous cell carcinoma. This neoplasia is an important differential diagnosis for esophageal lesions in birds. There are various carcinogens for squamous cell carcinoma such as sunlight, virus, some chemicals and chronic wounds, the last one being a possible cause of the squamous cell carcinoma in this rooster as no evidence of other etiologies were found.